The lateral preoptic area plays a dual role in the regulation of thirst in the rat - Saad, W. A.; Luiz, A. C.; Camargo, LAD; Renzi, Antonio [UNESP]; Manani, J. V. (Elsevier B.V., 1996)
Electrolyte lesion and ibotenic acid lesion of the lateral preoptic area (LPO) of the rat were used to study the participation of this area in drinking behavior. Drinking was induced by cellular dehydration, hypovolemia, hypotension, and water deprivation. The animals with electrolytic lesion of the LPO showed a significant reduction in water intake in response to cellular dehydration, hypotension, and deprivation. The animals with ibotenic acid lesion of the LPO increased the water consumption produced by subcutaneous (SC) injection of hypertonic saline. The amount of water intake after SC injection of polyethyleneglycol (PEG) or isoprenaline was similar in control and ibotenic acid-lesioned animals. The rats with ibotenic acid lesion of the LPO drank significantly more water than control animals. Fibers of passage may also influence the drinking response, and the LPO may have osmosensitive receptors that facilitate water intake in connection with other areas of the central nervous system (CNS) that are implicated in drinking behavior.
Keywords: lateral preoptic area; drinking behavior; osmoreceptors; electrolytic lesion; ibotenic acid